Effects of steel fiber on the flexural behavior and ductility of concrete beams reinforced with BFRP rebars under repeated loading. (15th August 2021) - Li, Zongze; Zhu, Haitang; Zhen, Xuanjiao; Wen, Chengcheng; Chen, Gang
Abstract: This study investigates the effects of concrete strength, steel fiber volume ratio, and steel fiber shapes on the flexural behavior and ductility of concrete beams reinforced with BFRP rebars under repeated loading with the aims of exploring the feasibility of using short discrete steel fiber to improve the ductility of beams, and proposing appropriate methods for evaluating their ductility. A four-point bending test was carried out on four steel fiber reinforced concrete (SFRC) beams with BFRP rebars and one beam reinforced with BFRP rebars only without steel fibers. Experimental results are reported in terms of the failure mode, flexural strength, load-deflection response, cracking behavior, and ductility, which reveals that the flexural strength of beams can be calculated using CSA S806-12 code method with an error of about 20%. Compared with ordinary concrete, the impact of steel fiber reinforcement on the service load of beams is more significant than that on their flexural strength; moreover, when steel fiber volume ratio increased from 0% to 1.0%, the deflection under service load decreased by 59.36%. In addition, the ductility of beam with 1.0% steel fiber volume ratio can be enhanced by 17% than that of concrete beam without steel fibers. Compared with energy ductility coefficient, displacement ductility coefficient, curvature ductility coefficient, the ductility coefficient of ACI 440.1R-15 prove to be more accurate in evaluating ductility of SFRC beams with BFRP rebars, and all the beams investigated in this study had a ductility factor greater than 4.0.